Analysis and design of a high-gain 100–180-GHz differential power amplifier in 130 nm SiGe BiCMOS. Issue 6 (10th February 2017) - Ahmed, Faisal; Furqan, Muhammad; Aufinger, Klaus; Stelzer, Andreas
Abstract : This paper presents the design and measurement results of a high-gain D-band broadband power amplifier (PA) implemented in a 130 nm SiGe BiCMOS technology. The topology of the PA is based on four differential cascode stages with interstage matching networks. A detailed analysis of the frequency behavior of the transimpedance-gain of the common-base stage of the cascode is presented by means of small-signal equivalent circuits, when the proposed four-reactance wideband matching network is used for output matching to the subsequent stage. The effect of the size of the active devices, in achieving a desired gain, bandwidth, and output power, is investigated. The fabricated D-band amplifier is characterized on-wafer demonstrating a peak differential gain and output power of about 25 dB and 11 dBm, respectively, while utilizing a DC power of 262 mW from a 2.7 V supply. The 3-dB small-signal bandwidth of the PA spans from 100 to 180 GHz (limited by the measurement setup), making it the first SiGe-based PA to cover the entire D-band frequency range. The PA achieves a state-of-the-art differential gain-bandwidth product of around 1.4 THz and the highest GBW/PDC ratio of 5.2 GHz/mW among all D-Band Si-based PAs.